2021
DOI: 10.1177/0333102421989232
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, controlled trial of lasmiditan over four migraine attacks: Findings from the CENTURION study

Abstract: Background We present findings from the multicenter, double-blind Phase 3 study, CENTURION. This study was designed to assess the efficacy of and consistency of response to lasmiditan in the acute treatment of migraine across four attacks. Methods Patients were randomized 1:1:1 to one of three treatment groups – lasmiditan 200 mg; lasmiditan 100 mg; or a control group that received placebo for three attacks and lasmiditan 50 mg for either the third or fourth attack. The primary endpoints were pain freedom at 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
88
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(103 citation statements)
references
References 14 publications
13
88
0
2
Order By: Relevance
“…Lasmiditan is a selective serotonin (5-HT 1F ) receptor agonist (ditan), approved in the US [1] and the United Arab Emirates for the acute treatment of migraine with or without aura in adults and being investigated in other geographies. In Phase 3 studies, lasmiditan was effective in the treatment of a migraine attack, as measured by pain freedom, pain relief, most bothersome symptom (MBS) freedom at 2 h, [2][3][4] and demonstrated a consistent response across attacks [4]. Common treatment emergent adverse events (TEAEs) were dizziness, paresthesia, somnolence, fatigue, nausea, muscular weakness, and hypoesthesia [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lasmiditan is a selective serotonin (5-HT 1F ) receptor agonist (ditan), approved in the US [1] and the United Arab Emirates for the acute treatment of migraine with or without aura in adults and being investigated in other geographies. In Phase 3 studies, lasmiditan was effective in the treatment of a migraine attack, as measured by pain freedom, pain relief, most bothersome symptom (MBS) freedom at 2 h, [2][3][4] and demonstrated a consistent response across attacks [4]. Common treatment emergent adverse events (TEAEs) were dizziness, paresthesia, somnolence, fatigue, nausea, muscular weakness, and hypoesthesia [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…In Phase 3 studies, lasmiditan was effective in the treatment of a migraine attack, as measured by pain freedom, pain relief, most bothersome symptom (MBS) freedom at 2 h, [2][3][4] and demonstrated a consistent response across attacks [4]. Common treatment emergent adverse events (TEAEs) were dizziness, paresthesia, somnolence, fatigue, nausea, muscular weakness, and hypoesthesia [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22] The CENTURION study demonstrated the consistency in efficacy and safety of lasmiditan treatment across multiple migraine attacks. 23…”
Section: Clinical Trialsmentioning
confidence: 99%
“…A summary of study design and endpoints is found in Ashina and colleagues. 23 The duration of the study was the treatment of 4 migraine attacks or 4 months, whichever occurred sooner. Patients were directed to treat their migraine within 4 hours of an attack of moderate to severe intensity and not repeat a dose until more than 48 hours after treatment of an attack to evaluate sustained pain freedom.…”
Section: Centurionmentioning
confidence: 99%
See 1 more Smart Citation